A cleaner process for lead recovery from lead-containing hazardous solid waste and zinc leaching residue via reducing-matting smelting. (20th December 2019) - Tang, Lei; Tang, ChaoBo; Xiao, Jin; Zeng, Ping; Tang, Motang; Wang, Zhian; Zhang, Zhenhua
Abstract: A large amount of lead paste, which is produced by waste lead-acid batteries, and zinc leaching residue are hazardous wastes that have not been effectively treated around the world. A cleaner production process (reducing-matting smelting) was first proposed to harmlessly co-treat lead-containing hazardous solid waste and zinc leaching residues. During reducing-matting smelting, iron-containing waste (zinc leaching residue) as sulfur-fixing agent to retain sulfur, which reduces sulfur dioxide generation and emissions. Thermodynamic analysis shows that reducing-matting process requires strong reduction atmosphere. Zinc leaching residue provides the iron, silicon and calcium required for the slagging. Lead-containing waste after roasting is mixed with zinc leaching residue for reducing-matting smelting. Under optimum smelting conditions (8 wt% coke, Ferrous oxide/Silicon dioxide = 1.8, Calcium oxide/Silicon dioxide = 0.6, smelting at 1350 ° C for 1.5 h), 92.4% of lead is recovered and fixed in the crude lead, lead content of slag drops to 1.2%. A portion of iron reacted with sulfur to form ferrous sulfide, most of the iron was present in the slag. This cleaner production technique also provides an alternative reference method for co-treatment of other lead waste containing sulfur. Graphical abstract: Image 101 Highlights: Sulfur-fixing agents reduces the production and emission of sulfur dioxide. Thermodynamic analysis confirms feasibility and reliability of the experiment. 92% of lead was recovered and lead content in slag decreased to 1.2%. Other valuable metals are also recovered when lead is recovered.